2018
DOI: 10.3390/ijgi7010028
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge Base for Automatic Feature Recognition from Point Clouds in an Urban Scene

Abstract: LiDAR technology can provide very detailed and highly accurate geospatial information on an urban scene for the creation of Virtual Geographic Environments (VGEs) for different applications. However, automatic 3D modeling and feature recognition from LiDAR point clouds are very complex tasks. This becomes even more complex when the data is incomplete (occlusion problem) or uncertain. In this paper, we propose to build a knowledge base comprising of ontology and semantic rules aiming at automatic feature recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The difference in the leaf inclination angle distribution between different parts within a tree was observed, and a detailed tree structural analysis was conducted. We found that this method enables accurate and efficient leaf inclination angle distribution.A 3D scanner called lidar (light detection and ranging) provides highly accurate and dense 3D point measurements [15,16]. The lidar is very useful for the retrieval of plant structural parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the leaf inclination angle distribution between different parts within a tree was observed, and a detailed tree structural analysis was conducted. We found that this method enables accurate and efficient leaf inclination angle distribution.A 3D scanner called lidar (light detection and ranging) provides highly accurate and dense 3D point measurements [15,16]. The lidar is very useful for the retrieval of plant structural parameters.…”
mentioning
confidence: 99%
“…A 3D scanner called lidar (light detection and ranging) provides highly accurate and dense 3D point measurements [15,16]. The lidar is very useful for the retrieval of plant structural parameters.…”
mentioning
confidence: 99%
“…[12]. Ontologies have been employed for solving various research problems such as GEographic Object-Based Image Analysis (GEOBIA) [13][14][15], information extraction and retrieval [16,17], information integration [18,19], linked data [20][21][22] and geoprocessing workflows [23], geospatial data provenance on the web [24], interpretation of natural language descriptions [25], automatic feature recognition from point clouds [26], and sketch map interpretation [27].…”
Section: Semantic Information Formalizationmentioning
confidence: 99%
“…Accurate recognition and localization of traffic signs are significant in intelligent traffic-related applications (e.g., autonomous driving [101] and driver-assisted systems), which help machines to respond in a timely and accurate manner in different situations. The high accuracy of points (about 1 cm) in the meter-level area along with imagery provides promising solutions for traffic sign detection (TSD) and recognition (TSR) while using mobile laser scanning techniques.…”
Section: Traffic Sign Detectionmentioning
confidence: 99%